The effects of diminazene aceturate and ceftriaxone on ram sperm - Tanyıldızı, S; Türk, G (My University, 2004)
Effects of diminazene aceturate and ceftriaxone disodium were evaluated on sperm quality of rams. Daily intramuscular injections of diminazene (6 mg/kg) or ceftriaxone (28.5 mg/kg) were given to each of seven Akkaraman rams assigned per drug for two days. Semen samples were collected from the rams at post-treatment 1, 4, 24, 48, 72, 144, 288 and 336 h and examined for sperm characteristics and hyaluronidase activity. Results showed that use of ceftriaxone and diminazene caused significant (P < 0:01) decreases in sperm concentration, volume and motility compared to control group within 288 h post-treatment. In addition, hyaluronidase activity increased significantly (P < 0:01) in semen of rams treated with ceftriaxone while remained unchanged in those received diminazene. In conclusion, diminazene aceturate and ceftriaxone disodium did not have any deleterious effect on hyaluronidase enzyme. However, both drugs caused impairment of sperm in rams during the 288 h.
Koç sperması üzerine diminazen aseturat ve seftriaksonun etkileri
Makale - Yabancı Dilde Makale
Keywords: diminazen ceftriaxone